Totally thrombosed giant P2 aneurysm: a case report and review of literature - (:unkn) unknown (My University, 2003)
The diagnosis and treatment of intracranial saccular giant aneurysms is still difficult despite developments in neuroradiology, neuroanesthesiology and micro-neurosurgery. These aneurysms are usually located on major intracranial arteries and are rarely on distal branches of these arteries. An extra-axial 4 x 5 cm mass lesion in the left mediobasal temporal region was detected on the CT and MRI examinations of a 37 year old male patient who was admitted to our institution with headache and slight right-sided hemiparesis lasting for 2 months. The lesion was avascular on angiography. Surgery proved that the lesion was a totally thrombosed giant aneurysm of the P2 segment of posterior cerebral artery (PCA). The P2 segment was clipped proximal to the aneurysm with pterional-transsylvian approach and the aneurysm was totally excised. Giant aneurysms of the P2 segment are rare and 15 cases have been reported in the literature. This report presents a rarely seen totally thrombosed giant P2 aneurysms and discusses the difficulties in diagnosis and treatment.
Keywords: Adult; Humans; Tomography, X-Ray Computed; Male; Magnetic Resonance Imaging; Thrombosis; Intracranial Aneurysm; Cerebral Angiography